Preventing violence against women and children : workshop summary - Patel, Deepali (The National Academies Press, 2011)
Violence against women and children is a serious public health concern, with costs at multiple levels of society. Although violence is a threat to everyone, women and children are particularly susceptible to victimization because they often have fewer rights or lack appropriate means of protection. In some societies certain types of violence are deemed socially or legally acceptable, thereby contributing further to the risk to women and children. In the past decade research has documented the growing magnitude of such violence, but gaps in the data still remain. Victims of violence of any type fear stigmatization or societal condemnation and thus often hesitate to report crimes. The issue is compounded by the fact that for women and children the perpetrators are often people they know and because some countries lack laws or regulations protecting victims. Some of the data that have been collected suggest that rates of violence against women range from 15 to 71 percent in some countries and that rates of violence against children top 80 percent. These data demonstrate that violence poses a high burden on global health and that violence against women and children is common and universal. Preventing Violence Against Women and Children focuses on these elements of the cycle as they relate to interrupting this transmission of violence. Intervention strategies include preventing violence before it starts as well as preventing recurrence, preventing adverse effects (such as trauma or the consequences of trauma), and preventing the spread of violence to the next generation or social level. Successful strategies consider the context of the violence, such as family, school, community, national, or regional settings, in order to determine the best programs.